2021
DOI: 10.1002/acr.24737
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions in Systemic Sclerosis: A Systematic Review and Future Directions

Abstract: Objective To systematically review evidence of rehabilitation interventions for improving outcomes in systemic sclerosis (SSc) and to evaluate evidence quality. Methods Several electronic databases were searched to identify studies in which rehabilitation professionals delivered, supervised, or participated in interventions for individuals with SSc. Randomized controlled trials (RCTs) or non‐randomized trials, one‐arm trials, and prospective quasi‐experimental studies with interventions were included if they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Rehabilitation is an important tool to help individuals manage scleroderma and potentially delay its disabling effects, including those involving the respiratory system [ 2 ]. One of the most important issues in the rehabilitation of patients with chronic diseases, including those with scleroderma, is regularity and repeatability, which can be more easily achieved by TOHR, especially during the current COVID-19 pandemic [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation is an important tool to help individuals manage scleroderma and potentially delay its disabling effects, including those involving the respiratory system [ 2 ]. One of the most important issues in the rehabilitation of patients with chronic diseases, including those with scleroderma, is regularity and repeatability, which can be more easily achieved by TOHR, especially during the current COVID-19 pandemic [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scleroderma is a chronic, progressive, and autoimmune disease characterized by cutaneous fibrosis, vasculopathy, and visceral damage [ 1 ]. Because it is an incurable condition, people with scleroderma need strategies to help manage the disease, such as rehabilitation, which plays an important role in improving the results reported by patients [ 2 ]. Physical activity has attracted increasing interest in recent years as an adjuvant therapy for people with scleroderma.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, only good or excellent quality studies were reported in its results, and it did not identify all available evidence on this topic. 25 This affected its conclusions, since they were biased by the selection of evidence and only included positive results. All 3 reviews had certain limitations: a small number of participants included in each study, generally high risk of bias across studies, and the use of alternative synthesis methods despite having data susceptible to meta-analysis.…”
Section: Interventions To Improve Different Outcomes In Individuals Withmentioning
confidence: 99%
“…The latter review synthesized rehabilitation interventions to improve different outcomes in individuals with SSc. Yet, only good or excellent quality studies were reported in its results, and it did not identify all available evidence on this topic 25 . This affected its conclusions, since they were biased by the selection of evidence and only included positive results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation